2012
DOI: 10.1177/0091270011399080
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Effects on Biochemical Markers of Bone Turnover and Pharmacokinetics of the Cathepsin K Inhibitor, ONO‐5334, in an Ascending Multiple‐Dose, Phase 1 Study

Abstract: Selective inhibitors of cathepsin K, which has a major role in the degradation of bone collagen, are potential new treatments for osteoporosis. The pharmacokinetics and the pharmacodynamic effects on biochemical markers of bone turnover of the new cathepsin K inhibitor, ONO-5334, were investigated in a multiple ascending dose, phase 1 study. A total of 120 healthy postmenopausal women were enrolled, and doses of 10 to 600 mg once daily and 50 and 300 mg twice daily were evaluated in 15- and 28-day multiple-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 14 publications
(25 reference statements)
5
21
0
Order By: Relevance
“…However, the peripheral concentrations of these markers under different clinical situations and treatment conditions do not always reflect the expected data. The relationship to the really observed bone mass and other circulating bone turnover markers has often been found contrary to their assumed regulative effect on osteoblasts [43][44][45][46]. Thus, the influence of biological factors (age, menopausal and hormonal status, renal function) on the concentration of both analytes in serum/plasma [47,48], the still not fully understood molecular processes in the bone [49,50], but also simply unresolved analytical problems [51] may currently be reasons for these substantial interpretation difficulties of the two analytes in serum/plasma.…”
Section: Sclerostin and Dickkopf-1 As Negative Regulatorsmentioning
confidence: 98%
“…However, the peripheral concentrations of these markers under different clinical situations and treatment conditions do not always reflect the expected data. The relationship to the really observed bone mass and other circulating bone turnover markers has often been found contrary to their assumed regulative effect on osteoblasts [43][44][45][46]. Thus, the influence of biological factors (age, menopausal and hormonal status, renal function) on the concentration of both analytes in serum/plasma [47,48], the still not fully understood molecular processes in the bone [49,50], but also simply unresolved analytical problems [51] may currently be reasons for these substantial interpretation difficulties of the two analytes in serum/plasma.…”
Section: Sclerostin and Dickkopf-1 As Negative Regulatorsmentioning
confidence: 98%
“…Mutations in CATHEPSIN K gene cause pycnodysostosis, a rare bone disease characterized by osteosclerosis and suppressed bone resorption [75]. Three inhibitors of cathepsin K are balicatib, whose development was stopped because of adverse effects due to lack of specificity inhibition of other cathepsins, odanacatib, and ONO5334 [76,77].…”
Section: New Therapeutic Horizonsmentioning
confidence: 99%
“…ONO-5334 is another cathepsin K inhibitor that has completed phase I and II clinical trials [65,66]. The phase II OCEAN clinical trial [66] demonstrated that this agent decreased bone resorption similar to alendronate, with little or no change in bone formation, in a dose ranging study.…”
Section: Cathepsin K Inhibitorsmentioning
confidence: 99%